2007
DOI: 10.1007/s10140-007-0636-7
|View full text |Cite
|
Sign up to set email alerts
|

Screening for aortic injury with chest radiography and clinical factors

Abstract: The purpose of this study was to evaluate the effectiveness and efficiency of a chest radiograph-based detection algorithm for aortic injury and to determine if a previously developed clinical prediction rule would improve imaging efficiency. A 3-year single institution retrospective case-control study with 25 cases of aortic injury and 181 controls was conducted. The detection algorithm correctly identified 96% of all cases of aortic injury, and a definitive diagnosis was established within 6h for 80% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The greater the blunt trauma force the higher the index of suspicion for TAI should be. 140 Initial plain chest X-rays have a significant false negative rate in patients with TAI. Consequently, once aortic…”
Section: Iib B 104mentioning
confidence: 99%
“…The greater the blunt trauma force the higher the index of suspicion for TAI should be. 140 Initial plain chest X-rays have a significant false negative rate in patients with TAI. Consequently, once aortic…”
Section: Iib B 104mentioning
confidence: 99%
“…Despite its relatively poor diagnostic accuracy [810] with significantly low specificity, it had been found to be the most powerful radiographic tool and improved specificity had been observed with the use of left mediastinal width (LMW) and mediastinal width ratio (MWR) [11]. Nevertheless, results from past literatures mainly focused on traumatic aortic rupture [12] but seldom on nontraumatic thoracic aortic rupture or aortic dissection which is far more common but often less emphasized with little attention received. In addition, the impact of posteroanterior (PA) and anteroposterior (AP) chest radiograph on mediastinal measurement was not well established and studied.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of ≤2 predictors inferred a TAI risk of <1 per cent . However, a subsequent evaluation of the rule concluded that the rule was not clinically useful, and found that only four of the composite variables were in fact significant predictors of TAI …”
Section: Resultsmentioning
confidence: 99%